THE EFFECT OF CONGKLAK GAMES ON THE COGNITIVE DEVELOPMENT OF EARLY CHILDHOOD - Najah, Adzro Fadila; Nuha, Alyaa Addien; Febrianty, Audry Eka Putri; Ferina, Ira; Sari, Tiara Naswa; Jayadinata, Asep Kurnia; Kurniati, Euis; Putri, Hafiziani Eka (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2026)
This study aims to evaluate the effectiveness of congklak as a learning medium for the cognitive development of children aged 5-6 years. Using a quantitative method with a One Group Pretest-Posttest pre-experimental design, the study involved eleven children at the Kota Ilmu Plus Kindergarten. The intervention was carried out for three weeks with a frequency of once per week, a duration of 30-45 minutes per session. Data were collected through structured observations measuring the ability to count, problem solving, logical thinking, focus, and memory. The results showed a decrease in the average score from 20.82 (Developing According to Expectations) in the pre-test to 15.82 (Starting to Develop) in the post-test, with an increase in variance from 11.76 to 84.76. A paired sample t-test showed a significant difference (t=2.355; p=0.040<0.05). The analysis identified internal factors (cognitive maturity, emotional state, motivation, learning style, concentration, physical condition, previous experience) and external factors (student grouping, time management, lesson planning, teacher competence) that influence learning outcomes. The study concluded that the effectiveness of the congklak game is highly dependent on the suitability of the application to the individual characteristics of the child and requires attention to supporting learning factors. A differentiated approach that considers the child's cognitive-emotional readiness, adequate time allocation, and responsive teaching strategies to individual needs is needed.